2012
DOI: 10.5815/ijmecs.2012.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Steganography Algorithm Using Randomized Intermediate QR Host Embedded With Any Encrypted Secret Message: ASA_QR Algorithm

Abstract: Due to tremendous growth in communication technology, now it is a real problem / challenge to send some confidential data / information through communication network. For this reason, Nath et al. developed several information security systems, combining cryptography and steganography together, and the present method, ASA_QR, is also one of them. In the present paper, the authors present a new steganography algorithm to hide any small encrypted secret message inside QR Code TM , which is then randomized and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…Moreover, the proposed scheme can preserve the original QR content by exploring the characteristic of the error correction capability of the QR tag. Table 6 displays the overall comparison between the related schemes [12][13][14][15][16] and the proposed scheme. Unlike the conventional hiding and watermarking schemes [9][10][11][12][13][14][15], the new scheme embeds the secret into the modules of the QR tag directly [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the proposed scheme can preserve the original QR content by exploring the characteristic of the error correction capability of the QR tag. Table 6 displays the overall comparison between the related schemes [12][13][14][15][16] and the proposed scheme. Unlike the conventional hiding and watermarking schemes [9][10][11][12][13][14][15], the new scheme embeds the secret into the modules of the QR tag directly [16].…”
Section: Resultsmentioning
confidence: 99%
“…The processes embed the secret into the pixels/coefficients and into the spatial/frequency domains of the host image. Such embedding algorithms, unfortunately, are unsuitable for the QR tag [9][10][11][12][13][14][15] due to the fact that the embedding schemes treat the QR tag as an image, in which the secret is concealed in the pixel or coefficients of the QR image without considering the characteristics of the QR modules. The decoding processes need further image processing, such as pixel and frequency transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of QR secret messages in steganography [10][11][12][13][14] is not original but the originality of the suggested methodology lies in the utilization of QR secret messages for achieving security levels in transmitting the secret message. This methodology imparts security levels on the secret message to be transferred securing it efficiently.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The data based scrambling methodologies are also reliable, where a data is created which is shared by both parties to communicate. Somdip Dey et al [14][30] suggested an advanced steganography methodology for embedding the message which involves message to undergo hidden, encoding into QR secret messages, scrambling and then embedding into cover image. The Least Significant Bit methodology is applied to imbed the bits of the secret message in a deterministic sequence, straight into the LSB (Least Significant Bit) plane of an image, referred as cover image.…”
Section: Literature Surveymentioning
confidence: 99%